Dynamic Vibration Characteristic Analysis for the Power-Split Transmission System Based on Loaded Tooth Contact Analysis. (19th October 2015) - Dong, Hao; Cao, Yan; Fang, Zhou
Abstract : In order to solve the dynamic vibration characteristics of the power-split transmission system, the system of the dynamic mechanical model is established. Firstly, according to the theoretical analysis method of the tooth contact analysis (TCA) and loaded tooth contact analysis (LTCA), the actual meshing process of each gear pair is simulated, and the time-varying mesh stiffness excitation is obtained, which can improve the numerical precision. Next, by using the lumped mass method, the bending-torsional coupling three-dimensional dynamical model of the power-split transmission is established. The identical dimensionless equations are deduced by eliminating the effect of rigid displacement and the method of dimensional normalization. Next, the frequency domain and time domain responses of this system are obtained. The dynamic load change characteristics of each gear pair are analyzed. The results show that establishment, solution, and analysis of the system dynamics model could provide a basis for the dynamic design and have an important significance for the dynamic efficiency analysis and dynamic performance optimization design of the power-split transmission. Through theoretical data compared with the experimental data, we verified the correctness of the method proposed.